Issues of Legal Regulation of Applying Coercive Measures of Medical Nature in International and Legal Acts and Legislation of Certain Foreign Countries - D. V. Turenko (Law and Safety)
The author has researched the main provisions of legal regulation in international and legal acts and national laws of some European Union countries and other foreign countries, where the possible application of coercive measures of a medical nature by courts, as well as decisions of the European Court of Human Rights on this category of criminal proceedings are regulated. The basic provisions, norms and differences of legal regulation of the application of coercive measures of medical nature in the legislation of certain foreign countries have been established. The implementation of international legal acts into national criminal, criminal procedural and other legislation has been analyzed. Based on the results of the research, the author has formulated a number of propositions and recommendations for the introduction into the legislative technique of Ukraine. Besides, the author has studied national theoretical issues of criminal law and criminal proceedings, as well as applied issues in this area of the research within law-enforcement activities of pre-trial investigation and inquiry agencies, prosecutor’s office and, in particular, procedural commissioners of pre-trial investigation. The scientific views of individual scholars and representatives of scientific schools on the researched issues have been also considered, and the relevant author’s opinions have been expressed. The author has characterized joint law-enforcement activities, problematic issues of law enforcement agencies and psychiatric medical institutions during the pre-trial investigation of criminal proceedings of this category, problematic issues and the existing system for providing psychiatric care to insane persons, as well as certain areas of cooperation in criminal and judicial proceedings. According to the results of the study, the author has suggested a number of propositions and recommendations for improving the theory of criminal law and criminal proceedings, law-enforcement activity and current criminal and criminal procedural legislation of Ukraine.